Chen, Cathy W. S. - (:unkn) unknown (My University, 2026)
Professor Cathy W.S. Chen is a distinguished Professor at Department of Statistics, Feng Chia University, Taiwan. She has made significant contributions to the areas of Bayesian inference, diagnostics and model comparison techniques for time series, as well as forecasting. She contributed to developing Bayesian methodology in econometrics and to applications of statistics to epidemiology research. Professor Chen has an internationally recognized record of research and scholarship as is demonstrated by the 106 papers published or accepted for publication in high quality academic journals. She became an Elected Member of International Statistical Institute (ISI) in 2008. In 2010, she was awarded with the Chartered Statistician (CStat) title which is the Royal Statistical Society's highest professional award. She is a fellow of the American Statistical Association and the Royal Statistical Society. Professor Chen is also making a large contribution to the profession through her editorial work. She is an Associate Editor of a number of prominent journals, including the following highly regarded journals: Journal of Business and Economic Statistics, Computational Statistics & Data Analysis, the Australian and New Zealand Journal of Statistics, PLOS ONE, and Computational Statistics.